2022
DOI: 10.3390/molecules27196662
|View full text |Cite
|
Sign up to set email alerts
|

The Norsesquiterpene Glycoside Ptaquiloside as a Poisonous, Carcinogenic Component of Certain Ferns

Abstract: Previous studies related to the ptaquiloside molecule, a carcinogenic secondary metabolite known from the world of ferns, are summarised. Ptaquiloside (PTA) belongs to the group of norsesquiterpenes of the illudane type. The name illudane refers to the fungal taxa from which the first representatives of the molecular group were identified. Ptaquiloside occurs mainly in Pteridium fern species, although it is also known in other fern taxa. The species of the genus Pteridium are common, frequent invasive species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The norsesquiterpene glycoside ptaquiloside has been extensively investigated for its potential carcinogenic properties [ 1 , 102 , 103 , 104 , 105 ]. Ingesting large quantities or prolonged consumption of ptaquiloside can be toxic to humans, emphasizing the need for caution when considering the edibility of bracken fern.…”
Section: Pharmacological Activity and Toxicitymentioning
confidence: 99%
See 3 more Smart Citations
“…The norsesquiterpene glycoside ptaquiloside has been extensively investigated for its potential carcinogenic properties [ 1 , 102 , 103 , 104 , 105 ]. Ingesting large quantities or prolonged consumption of ptaquiloside can be toxic to humans, emphasizing the need for caution when considering the edibility of bracken fern.…”
Section: Pharmacological Activity and Toxicitymentioning
confidence: 99%
“…Guinea pigs, unlike rats or mice, exhibit hemorrhagic cystitis and hematuria upon subcutaneous administration of ptaquiloside [ 110 ]. It has been suggested that ptaquiloside accounts for more than half of the mutagenic potency associated with bracken [ 1 , 102 , 105 ]. Although a comprehensive modern carcinogenicity bioassay of ptaquiloside is lacking, limited studies in rats have explored its carcinogenicity.…”
Section: Pharmacological Activity and Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…PTA is observed in the whole tissue of BF, low in roots and spores, and high in edible parts, crosiers [ 21 , 22 ]. Fortunately, PTA is degraded to a stable form by hydrothermal methods [ 23 , 24 , 25 ] and is expected to exhibit reduced toxicity.…”
Section: Introductionmentioning
confidence: 99%